Financial Relationships between Urologists and Industry: An Analysis of Open Payments Data. Issue 3 (May 2018) - Maruf, Mahir; Sidana, Abhinav; Fleischman, William; Brancato, Sam J.; Purnell, Stephanie; Agrawal, Shantanu; Agarwal, Piyush K.
Abstract : Introduction: : The Open Payments Program was enacted to increase transparency of financial relationships between physicians and the medical device and pharmaceutical industry. We examined nonresearch related financial relationships between urologists and industry in the United States using the latest Open Payments data. Methods: : We performed a descriptive analysis of Open Payments data released by the Centers for Medicare and Medicaid Services for 2014. Total payment amounts associated with various urological drug and device categories were calculated. We then examined for correlations between payments and prescribing at the national level using Medicare Part D prescribing data. Results: : There were 232, 207 payments totaling $32, 418, 618 made to 8, 618 urologists (73.6% of practicing urologists in the United States) during calendar year 2014. Median payment was $15 (IQR $11 to $24). While the majority of individual payments (68%) were $20 or less, 82% of the urologists in the database received more than $100 from industry during 2014. The frequency of industry payments was positively correlated with Medicare Part D prescribing frequency as well as the sum of claims (r = 0.726, p = 0.005 and r = 0.755, p = 0.003, respectively). Conclusions: : Nearly 75% of urologists in United States received nonresearch payments from industry in 2014. Most individual payments were for less than $20 but the majority of urologists received more than $100 in aggregate during the study year, with most of the money going toward speaker fees. Payments were positively correlated with Part D prescribing, yet confounding variables make it difficult to establish a cause and effect relationship.